Enseignements du PIRLS-2021 sur la littéracie en lecture des élèves de 4e année: Comparaisons Québec, trois provinces canadiennes, six pays européens - Pierre Lefebvre; Philip Merrigan (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Groupe de recherche sur le capital humain (GRCH), 2023)
The latest international survey in education - PIRLS 2021 - is the first to present an international comparative study of fourth grade students' reading achievement that coincided with the height of the COVID-19 pandemic. Tests results confirm the general prediction for a majority of jurisdictions that students would have a lower performance than in the 2006 survey. Results are analysed by subject: scores achievement (mean, trends, percentiles, international benchmarks); relationship between scores and socioeconomic environment (students, schools), parental factors (early Literacy Activities, academic expectations), and school composition (resources, academic emphasis, discipline and security). Constructed and commented tables and statistics are presented on a comparative basis for 11 jurisdictions: four Nordic countries (Denmark, Finland, Norway, Sweden), two Belgian regions (Flemish, French), France, and four Canadian provinces (BritishColumbia, Alberta, Québec, Newfoundland-Labrador). Canadian students and their schools generally are among those having the highest scores, which express the resilience of their schooling systems. Socioeconomic achievement gaps are among the lowest, especially in Québec where scores have increased. The analysis also presents job satisfaction and perceptions on the profession by teachers, as well as the number of weeks with schools pandemic perturbations.
Keywords: 330